İŞBİRLİKLİ ÖĞRENME VE MODELLERİN KİMYASAL REAKSİYONLAR KONUSUNUN ANLAŞILMASINA ETKİSİ. - OKUMUŞ, Seda; ÇAVDAR, Oylum; ALYAR, Mustafa; DOYMUŞ, Kemal (Mehmet Akif Ersoy University Journal of Education Faculty, 2017)
It was investigated the effects of cooperative learning and models on students' understanding related to the chemical reactions in this study. Research sample was comprised of 65 students from the first grade of science teacher education program. Quasi-experimental method with pre and posttest was used. Groups was determined as cooperative learning group-CLG (N=20), cooperative learning and model group-CLMG (N=22) and a control group-CG (N=23). An open-ended drawing test (the particulate nature of matter drawing test-PNMDT) which related to chemical reactions was used to collect data. Expert's views were gathered to determine validity of the PNMDT, internal consistency of scores were calculated for determining reliability of the test. Before the application the PNMDT was implemented as pre-test, after the application the PNMDT was implemented as posttest. According to ANOVA results, although pre-test results showed no significant difference between groups (p>0.05), there was a significant difference between CLMG and CG (CLMG positively different from CG) and between CLG and CG (CLG positively different from CG) in posttest results (p<0.05). Also, it was seen that some students' misconceptions still continue after the implementation.